Energieffektivisering inom sjöfarten - En undersökning av sociotekniska barriärer ombord ett passagerarfartyg - Schrewelius, Fredrik (My University, 2016)
The climate threat grows every mile a ship lay behind and shipping has fallen behind in its environmental work in relation to other industries and road transport. In these segments development has progressed while large parts of the global fleet are still steaming with old ships and environmentally disastrous fuel oil with its massive carbon dioxide emissions. An important part in bringing down the carbon dioxide emissions is then to make the ships more energy efficient so that less of the environmentally hazardous fuel oil is spent. This study will try to highlight the energy efficiency gap on board a ship, in other words the gap that exists between available efficiency technologies/equipment and the use or implementation of this technology/equipment, and the socio-technical barriers which perpetuate the gap's size and scope. Do the crew of the ship have any participation in the gap? Are they aware of what energy efficiency means and are they doing something to reduce the carbon dioxide emissions? To explore this, interviews were conducted with members of the crew in command post aboard the ship in the autumn of 2015. The ship is staffed with a Swedish crew and run regular routes between Sweden and Europe for a fixed timetable. The answers from the interviews reveal that the crew is overall unanimous in that they see improving energy efficiency as a positive challenge, but it is difficult to accomplish anything on the subject because of the current schedule the ship operates with. The crew considers itself generally that they do not have the right conditions or powers to influence energy consumption. The will to do it, however, is good in all and most of them see it as a positive development that the demand to be energy efficient is raised. The crew also revealed many ideas for improvements and suggestions on buying equipment that would directly or indirectly reduce energy consumption.
Keywords: Transportteknik och logistik; Energi; Hållbar utveckling; Transport; Transport Systems and Logistics; Energy; Sustainable Development; Transport